Preparation method and application of porous Nb2O5-coated S composite active material

Porous Nb2O5 material was prepared by wet impregnation heat treatment method and melt-combined with sulfur to prepare porous Nb2O5@S composite active material, which was used for the positive electrode of lithium sulfur battery, solving the problems of short battery cycle life and low sulfur utilization rate, and achieving efficient battery performance and long life.

CN119725533APending Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311279091.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The battery cycle life of lithium sulfur and sodium sulfur batteries is short and the sulfur utilization rate is low, mainly due to the shuttle between the intermediate product polysulfide and its reaction kinetics.

Method used

The porous Nb2O5 material was prepared by wet impregnation heat treatment method, and the porous Nb2O5@S composite active material was prepared by mixing melt composite with sulfur, as the positive electrode material of lithium sulfur batteries.

Benefits of technology

The discharge specific capacity and sulfur load capacity of lithium-sulfur batteries are improved, the efficiency performance and sulfur utilization rate of Coulombs are performed, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725533A_ABST
    Figure CN119725533A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a porous Nb2O5-coated S composite active material. The preparation method comprises the following steps: (1) preparing a porous Nb2O5 material by adopting a wet impregnation heat treatment method; and (2) mixing the porous Nb2O5 material with sulfur, melting and compounding to obtain the porous Nb2O5-coated S composite active material. Sulfur and porous framework Nb2O5 particles are fully and uniformly mixed through ball milling, the sulfur electrode is prepared through a binder fibrillation method, the higher sulfur loading amount can be obtained, and the catalytic reaction efficiency of sulfur is improved. In addition, due to the existence of a heterogeneous interface, the material has excellent electron conduction capability and better adsorption and catalysis effects on polysulfide, and the sulfur utilization rate and the service life of a sulfur electrode can be greatly improved and prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method and application of a porous Nb2O5@S composite active material, belonging to the field of electrochemical energy technology. Background Art

[0002] With global climate change, humans are disgusted by the various climate disasters caused by the use of fossil fuel energy, and the need for clean, efficient and renewable energy is increasing. Therefore, a large number of wind and solar power stations have been built across the country, and new energy vehicles have been vigorously promoted across the country. However, these new energy sources are intermittent in time and space, and it is difficult to directly connect to the power grid for application. Therefore, like new energy vehicles, it is urgent to develop a suitable energy storage system. Various emerging energy storage devices, such as lithium-ion batteries, zinc-ion batteries, sodium-ion batteries and various metal batteries have received widespread attention, among which lithium-sulfur and sodium-sulfur batteries have attracted much attention due to their ultra-high theoretical specific capacity. The main obstacle to the realization of the high theoretical specific capacity of lithium-sulfur and sodium-sulfur batteries is the short battery cycle life caused by the shuttle of intermediate products polysulfide and their poor reaction kinetics. Therefore, the development of a sulfur electrode with good stability, high sulfur utilization rate and long life is crucial for the practical application of lithium-sulfur and sodium-sulfur batteries. At present, there have been a lot of related research on related issues, such as solving the problems of sulfur electrodes by adding catalysts to accelerate the reaction, adding conductive agents to increase conductivity, adding porous polymers to control polysulfide shuttling and sulfur volume changes, etc., which is of great significance to the development and application of batteries using sulfur electrodes.

[0003] Transition metal oxides are widely used as sulfur electrode carriers due to their good stability, but the conductivity of transition metal oxides is poor, and transition doping will reduce the conductivity of the electrode. Therefore, developing a transition metal oxide material with good conductivity as a sulfur carrier has important practical significance for the application of sulfur positive electrodes. Summary of the invention

[0004] In order to solve the above-mentioned problems existing in sulfur electrodes, the present invention provides a method for preparing a sulfur dry electrode containing a porous skeleton Nb2O5 composite material. When the electrode obtained by the method is applied to a lithium-sulfur battery, it exhibits higher discharge specific capacity and sulfur loading, higher coulombic efficiency performance and sulfur utilization rate.

[0005] According to the first aspect of the present application, a method for preparing a porous Nb2O5@S composite active material is provided, the preparation method comprising the following steps:

[0006] (1) Preparing porous Nb2O5 materials by wet impregnation heat treatment;

[0007] (2) The porous Nb2O5 material is mixed with sulfur, and melt-compounded to obtain the porous Nb2O5@S composite active material.

[0008] Optionally, in step (1), the method for preparing the porous Nb2O5 material comprises:

[0009] The porous Nb2O5 material is obtained by ultrasonically impregnating, drying and calcining a mixture containing niobium pentachloride, porous carbon and a solvent.

[0010] Optionally, the mass ratio of the porous Nb2O5 material to sulfur is 1:6 to 2:3.

[0011] Optionally, the mass ratio of the niobium pentachloride to the porous carbon is 1:0.1-2.

[0012] Optionally, the porous carbon is selected from at least one of Ketjen black, carbon nanotubes, activated carbon, and carbon molecular sieves.

[0013] Optionally, the solvent is selected from at least one of ethanol, methanol and isopropanol.

[0014] Optionally, the concentration of the solution formed by the niobium pentachloride and the solvent is 50-300 mM.

[0015] Optionally, the ultrasonic immersion time is 0.5 to 6 hours.

[0016] Optionally, the drying temperature is 60 to 100° C., and the drying time is 10 to 48 hours.

[0017] Optionally, the calcination temperature is 600-700° C., and the calcination time is 0.5-2 h.

[0018] Optionally, in the step (2), the porous Nb2O5 material is mixed with sulfur in an inert atmosphere and placed in a closed reactor for melt compounding to obtain the porous Nb2O5@S composite active material.

[0019] Optionally, the inert atmosphere is selected from at least one of nitrogen, argon and helium.

[0020] Optionally, in step (2), the temperature of the melt compounding is 155 to 180° C., and the time of the melt compounding is 12 to 15 hours.

[0021] The present invention provides a method for preparing a porous skeleton Nb2O5 composite material, the method comprising the following steps:

[0022] S1. In an argon atmosphere, weighed niobium pentachloride is placed in a reagent bottle, a certain amount of anhydrous ethanol is added, the bottle cap is tightened, and ultrasonic dispersion is performed to obtain a solution A;

[0023] S2, adding a certain proportion of porous carbon to the solution A obtained in step S1, tightening the bottle cap, and ultrasonically impregnating to obtain a precursor solution B;

[0024] S3, placing the precursor solution B obtained in step S2 in a vacuum oven for drying at a temperature of 80°C;

[0025] S4. After the precursor in step S3 is dried, the precursor is ground into powder, then loaded into a crucible and placed in an argon tube furnace for high-temperature sintering. After natural cooling, the sample is taken out and ground into powder.

[0026] Optionally, in step S1, the concentration of solution A is 50-300 mM.

[0027] Optionally, in step S2, the added porous carbon is calculated based on the mass of niobium pentachloride, and the mass ratio of niobium pentachloride to porous carbon is about 1:0.1 to 1:2.

[0028] Optionally, in step S2, each ultrasonication time shall not be less than 0.5 h.

[0029] According to a second aspect of the present application, a lithium-sulfur battery positive electrode sheet is provided, wherein the lithium-sulfur battery positive electrode sheet contains a composite active material;

[0030] The composite active material is selected from the porous Nb2O5@S composite active material described above.

[0031] In the present application, a composite material formed by combining a porous skeleton Nb2O5 and S prepared by the above method is provided. The specific implementation steps are:

[0032] 60% to 95% of S is mixed evenly with Nb2O5, and then melt-compounded in an argon environment to obtain a composite active material of Nb2O5 and S.

[0033] In a specific embodiment, the melt reaction temperature is 155° C. and the time is 12 hours.

[0034] According to a third aspect of the present application, a method for preparing the above-mentioned lithium-sulfur battery positive electrode sheet is provided, the preparation method comprising:

[0035] The composite active material, the binder and the conductive agent are mixed and a lithium-sulfur battery positive electrode sheet is prepared by a dry method.

[0036] Optionally, the mass ratio of the composite active material, the conductive agent and the binder is: 60-98:35-1:20-1.

[0037] Optionally, the conductive agent includes but is not limited to Super P, carbon fiber (VGCF), carbon nanotube (CNT), Ketjen black, graphene and the like.

[0038] Optionally, the binder includes but is not limited to polytetrafluoroethylene (PTFE), copolymers of tetrafluoroethylene and other monomers (such as ethylene, hexafluoropropylene), etc.

[0039] Optionally, the sulfur electrode material comprises 60 to 98 parts by weight of the composite active material, 1 to 35 parts by weight of a conductive agent, and 1 to 20 parts by weight of a binder.

[0040] In the present application, the sulfur electrode material should be premixed first, then sheared and mixed by high-speed airflow to fiberize the material to obtain flocculent powder, and then pre-rolled and rolled to obtain a film, and finally the film is laminated with carbon-containing aluminum foil to form a dry electrode.

[0041] According to a fourth aspect of the present application, there is provided a use of the above-mentioned lithium-sulfur battery positive electrode sheet in a lithium-sulfur battery.

[0042] The present invention provides a method for preparing a dry sulfur electrode sheet by compounding porous skeleton Nb2O5 particles prepared by an impregnation heat treatment technology with sulfur. The porous skeleton Nb2O5 particles obtained are ground and mixed with sulfur powder, and then melt-compounded to obtain an active material, which is then mixed with a conductive agent and a binder in a certain proportion, and then subjected to high-speed airflow milling, pre-roll thinning, and current collector compounding to obtain an electrode sheet. The present invention fully and evenly mixes sulfur and porous skeleton Nb2O5 particles by ball milling, and prepares a sulfur electrode by a binder fibrillation method, which can obtain a higher sulfur loading and improve the catalytic reaction efficiency of sulfur. In addition, due to the presence of a heterogeneous interface, the material has excellent electronic conductivity, better adsorption and catalytic effects on polysulfides, and can significantly improve the sulfur utilization rate and service life of the sulfur electrode.

[0043] The beneficial effects of this application include:

[0044] In the present invention, a porous skeleton Nb2O5 material is firstly synthesized by wet impregnation heat treatment technology, and then sulfur (S) powder and Nb2O5 are uniformly mixed and melted in an argon environment to obtain a composite active material.

[0045] The active material of the present invention is used to prepare a battery using a sulfur electrode, which shows excellent cycle performance and rate performance, and has an ultra-long service life. In addition, compared with the wet electrode preparation process, the dry electrode preparation process adopted by the present invention does not require the use of solvents, reduces the use of toxic organic solvents, and is beneficial to the health of experimental operators. At the same time, compared with other dry processes and electrodes prepared by wet processes, it is more suitable for large-scale preparation, and has low energy consumption, controllable thickness and ideal surface capacity density. Therefore, the present invention has important value in developing practical lithium-sulfur and sodium-sulfur batteries and materials in the field of related energy storage and conversion.

[0046] The dry sulfur electrode of the present invention has the above-mentioned excellent properties, the essence of which is that the porous skeleton Nb2O5 has good catalytic performance, and the presence of heterogeneous interface and porous carbon enhances its conductivity, effectively accelerates the conversion of solid sulfur element into polysulfide, solves the problem of slow reaction kinetics of sulfur electrode, and realizes the rapid reaction of sulfur electrode battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is the XRD diagram of the Nb2O5 composite material prepared in Example 1 of the present application.

[0048] Figure 2 This is the SEM image of the Nb2O5 composite material prepared in Example 1 of the present application.

[0049] Figure 3 This is a graph showing the long cycle performance of a composite material of Nb2O5 composite material and sulfur powder prepared in Example 1 of the present application as a positive electrode material for a lithium-sulfur battery. DETAILED DESCRIPTION

[0050] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0051] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0052] The conductive carbon used was purchased high-density conductive carbon black Super P, the porous carbon used was purchased from Xianfeng Technology EC600, and the XRD powder diffractometer test used Bruker D8 (Cu Kα, ), the material structure morphology was obtained using a Zeiss Sigma500 scanning electron microscope, and the constant current charge and discharge test was performed using a NEWARE CT-4800 battery test system with a voltage test range of 1.7-2.8V.

[0053] Example 1

[0054] (1) Under argon atmosphere, weigh 202.5 mg of niobium pentachloride and put it into a reagent bottle. At the same time, add 5 mL of anhydrous ethanol, tighten the bottle cap, and perform ultrasonic dispersion for 2 h to prepare solution A.

[0055] (2) After the ultrasonic treatment in step (1) is completed, 81 mg of EC600 porous carbon is added to solution A, the bottle cap is tightened, and ultrasonic immersion is performed for 3 h to obtain precursor solution B.

[0056] (3) After the ultrasonic treatment in step (2) is completed, the precursor solution is placed in a vacuum oven and dried at 60° C. for 24 h to obtain a precursor.

[0057] (4) The precursor obtained after drying in step (3) was ground into powder, loaded into a crucible and placed in a tube furnace, argon gas was introduced, and the temperature was kept at 650° C. for 1 h at a heating rate of 10° C. / min, and naturally cooled to obtain a Nb2O5 composite material.

[0058] (5) Grind 194 g of the Nb2O5 composite material obtained in step (4) into powder, and then ball-mill it with 582 g of S powder in a ratio of 1:3 for 6 h. Mix them evenly, then place them in a reactor, replace the gas therein with argon, place them in an oven, and perform a melting reaction at 155°C for 12 h. After natural cooling, the Nb2O5 / S composite active material is obtained.

[0059] (6) 776 g of the Nb2O5 / S active material obtained by sulfur injection in step (5) was pre-mixed with 8 g of conductive carbon Super P and 16 g of binder PTFE in a blade mixer in a ratio of 97%, 1% and 2% at a stirring speed of 500 rpm for 30 min.

[0060] (7) The mixed material obtained after stirring in step (6) is added into a jet mill, and the four-way high-speed airflow provides shear force to pulverize the material and make it fiberized.

[0061] (8) The powder obtained from the jet mill in step (7) is placed in an oven for high-temperature mixing at 230 degrees Celsius for 30 minutes until the material has a slightly agglomerated feel.

[0062] (9) The bulk agglomerated powder after high-temperature internal kneading in step (8) is placed in a high-temperature double-roller press for high-temperature pre-rolling treatment to form a film.

[0063] (10) Cut the film pre-rolled in step (9) into regular shapes, put it into a high-temperature double-roller press, and perform low-speed rolling and thinning to obtain a positive electrode film of the desired thickness.

[0064] (11) The positive electrode film thinned in step (10) is placed on a carbon-containing aluminum foil current collector, and is placed in a roller press for current collector lamination to obtain a positive electrode sheet.

[0065] (12) The positive electrode sheet obtained in step (10) is cut into a positive electrode sheet with a diameter of 12 mm and assembled with a separator and a lithium sheet into a lithium-sulfur battery for subsequent electrochemical performance testing. The battery assembly is carried out in a glove box filled with argon (water and oxygen values ​​are all less than 0.01 ppm), a 2032 button battery shell is selected, Celgard 2500 is used as a separator, a metal lithium sheet is used as a negative electrode, and the electrolyte is a mixed solvent with a volume ratio of 1,3 dioxolane: ethylene glycol dimethyl ether = 1:1 (DOL:DME) and 1M lithium bistrifluoromethanesulfonyl imide (LiTFSI) and 1% lithium nitrate (LiNO3) by mass.

[0066] The performance test results of the Nb2O5 composite material and the lithium-sulfur battery positive electrode obtained in Example 1 are as follows: Figures 1 to 3 shown.

[0067] from Figure 1 It can be seen that the Nb2O5 embedded in the Nb2O5 composite material obtained in Example 1 is a hexagonal crystal structure.

[0068] from Figure 2 It can be seen that the Nb2O5 composite material obtained in Example 1 has abundant pores, and the Nb2O5 particles are evenly distributed in the pores.

[0069] from Figure 3 It can be seen that after the Nb2O5 composite material obtained in Example 1 is filled with sulfur, the assembled battery has a coulombic efficiency close to 100% and still maintains a high specific capacity after 500 cycles.

[0070] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a porous Nb2O5@S composite active material, characterized in that: The preparation method comprises the following steps: (1) Preparing porous Nb2O5 materials by wet impregnation heat treatment; (2) The porous Nb2O5 material is mixed with sulfur, and melt-compounded to obtain the porous Nb2O5@S composite active material.

2. The preparation method according to claim 1, characterized in that: In the step (1), the method for preparing the porous Nb2O5 material comprises: The porous Nb2O5 material is obtained by ultrasonically impregnating, drying and calcining a mixture containing niobium pentachloride, porous carbon and a solvent.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the porous Nb2O5 material to sulfur is 1:6 to 2:

3.

4. The preparation method according to claim 2, characterized in that: The mass ratio of niobium pentachloride to porous carbon is 1:0.1-2; Preferably, the porous carbon is selected from at least one of Ketjen black, carbon nanotubes, activated carbon, and carbon molecular sieves; Preferably, the solvent is selected from at least one of ethanol, methanol and isopropanol; Preferably, the concentration of the solution formed by the niobium pentachloride and the solvent is 50-300 mM.

5. The preparation method according to claim 2, characterized in that: The ultrasonic immersion time is 0.5 to 6 hours; Preferably, the drying temperature is 60-100°C and the drying time is 10-48h; Preferably, the calcination temperature is 600-700° C., and the calcination time is 0.5-2 h.

6. The preparation method according to claim 1, characterized in that: In the step (2), the porous Nb2O5 material is mixed with sulfur in an inert atmosphere and placed in a closed reactor for melt compounding to obtain the porous Nb2O5@S composite active material; Preferably, the inert atmosphere is selected from at least one of nitrogen, argon and helium; Preferably, in the step (2), the temperature of the melt compounding is 155 to 180° C., and the time of the melt compounding is 12 to 15 hours.

7. A lithium-sulfur battery positive electrode sheet, characterized in that: The lithium-sulfur battery positive electrode sheet contains a composite active material; The composite active material is selected from the porous Nb2O5@S composite active material according to any one of claims 1 to 6.

8. The method for preparing the positive electrode sheet of a lithium-sulfur battery according to claim 7, characterized in that: The preparation method comprises: The composite active material, the binder and the conductive agent are mixed and a lithium-sulfur battery positive electrode sheet is prepared by a dry method.

9. The method for preparing a lithium-sulfur battery positive electrode sheet according to claim 8, characterized in that: The mass ratio of the composite active material, the conductive agent and the binder is 60-95:35-1:20-2.

10. Use of the lithium-sulfur battery positive electrode sheet according to claim 7 in lithium-sulfur batteries.

Citation Information

Patent Citations

  • Preparation method of nanofiber-like niobium pentoxide / sulfur composite positive electrode material

    CN108172796A

  • Positive electrode material layer, preparation method thereof, positive plate and battery

    CN112289976A

  • Niobium-based metal oxide mesoporous carbon sphere composite material and sodium ion battery negative electrode material containing niobium-based metal oxide mesoporous carbon sphere composite material

    CN114300665A

  • Lithium-sulfur battery containing an electrode-protecting layer

    US20200028178A1